e Relationship Between Physical Activity And Eating Patterns With Nutritional Status Of Adolescent Girls - Handayani, Sri; Pratiwi, Yopi Suryatim; Gusmiya Aisyafitri, Sherly Masryabina (JKM (Jurnal Kebidanan Malahayati), 2025)
Latar Belakang: Prevalensi masalah status gizi pada remaja putri masih tinggi di Indonesia. Tingginya masalah status gizi disebabkan kebiasaan makan aktivitas fisik yang berdampak terhadap penurunan imunitas dan produktivitas. Remaja memiliki perilaku konsumsi pangan yang tidak sesuai dengan kebutuhan.Tujuan: Penelitian ini bertujuan untuk mengetahui hubungan pola makan dan aktivitas fisik dengan status gizi remaja putri. Metode:  Metode yang digunakan dalam penelitian ini adalah kuantitatif dengan pendekatan cross sectional. Sampel dalam penelitian ini berjumlah 117 responden. Instrumen pengukuran pola makan menggunakan kuesioner semi FFQ, aktivitas fisik menggunakan kuesioner PAQ-A, dan status gizi diukur berdasarkan IMT perumur.   Karakteristik responden yaitu pola makan, akivitas fisik, dan status gizi dianalisis secara univariat dan disajikan dalam tabel distribusi frekuensi, sedangkan analisis bivariat menggunakan uji Chi Square.Hasil: Hasil penelitian menujukkan sebagian besar remaja putri mempunyai pola makan yang tidak sesuai dengan PGS, yaitu sebanyak 84 (72%) remaja putri, memiliki aktivitas yang aktif sebesar 72 (62%), dan sebagian besar berstatus gizi normal sebanyak 90 (77%) remaja putri. Analisis bivariat hubungan antara pola makan dan aktivitas fisik dengan status gizi menunjukkan nilai p< 0,05 yang berarti terdapat hubungan yang signifikan antara pola makan dan aktivitas fisik dengan status gizi remaja.Kesimpulan: Berdasarkan hasil penelitian dapat disimpulkan pola makan dan aktivitas fisik berhubungan dengan status gizi.Saran: Diharapkan semua remaja putri untuk mengatur pola makan dan aktif melakukan aktivitas fisik untuk memperbaiki status gizi. Kata Kunci : Aktivitas Fisik; Pola Makan; Remaja; Status Gizi ABSTRACT Background:  The prevalence of nutritional status problems among teenage girls is still high in Indonesia. The high nutritional status problems are caused by eating habits and physical activity that affect immunity and productivity. Teenagers have food consumption behaviors that do not align with their needs.Purpose:  This research aims to determine the relationship between eating patterns and physical activity with the nutritional status of adolescent girls.Methods:  The method used in this study is quantitative with a cross-sectional approach. The sample in this study consisted of 117 respondents. The measurement instrument for dietary patterns used a semi-FFQ questionnaire, physical activity was assessed using the PAQ-A questionnaire, and nutritional status was measured based on BMI for age. The characteristics of the respondents, namely dietary patterns, physical activity, and nutritional status, were analyzed univariately and presented in frequency distribution tables, while the bivariate analysis used the Chi Square testResults: The research results show that the majority of adolescent girls have eating patterns that do not conform to the PGS, with 84 (72%) adolescent girls having an active lifestyle of 72 (62%), and most having a normal nutritional status amounting to 90 (77%) adolescent girls. The bivariate analysis of the relationship between eating patterns and physical activity with nutritional status shows a p-value < 0.05, indicating a significant relationship between eating patterns and physical activity with the nutritional status of adolescents.Conclusion: Based on the research findings, it can be concluded that diet and physical activity are related to nutritional status. Suggestions: It is hoped that all adolescent girls will manage their diet and actively engage in physical activities to improve their nutritional status. Keywords: Physical Activity; Eating Patterns; Adolescents; Nutritional Status